Perencanaan Distribusi Air Sumur Bor Desa Cibunar Kecamatan Cibatu - Ahmad Rosidin; Sulwan Permana (Jurnal Konstruksi, 2024)
Clean water plays a very important role in everyday life. However, the dry season causes a water crisis in several areas of Garut Regency, one of which is Cibunar Village, Cibatu District. The aim of this research is to plan drinking water discharge needs, storage tank capacity and water distribution planning by maximizing the potential of drilled well water as a source of raw water. There is a need for distribution engineering with PVC pipe networks and combined drainage systems. In planning this network, population projections use the geometric method for the 2023-2042 plan year with a population at the end of the plan year of 11,191 people, the total water requirement per person is 60 liters/person/day. The total domestic water requirement for one village is 671,460 liters/person/day or 7.77 liters/second at the end of the 2042 projected plan year. The complete data was then analyzed using the EPANET 2.2 application, the results of the analysis obtained the average pressure 25.23 m, average head loss 0.56 km/m and average flow speed 0.18 m/s and from the results of this analysis the ideal diameter of the distribution pipe is 100-200 mm. Meanwhile, the results of running with the peak hour scenario obtained a flow of 879 liters/hour. In planning the pump specifications required a total head of 159.34 m and a power of 45.41 Kw with pump type CR 120-5-1. Cibunar Village distribution network planning at the end of the planning year can meet community needs during the planning period.